PROSPECTIVE INVESTIGATION OF PRECONTOURED LOCKING COMPRESSION PLATES USED TO TREAT CLAVICLE FRACTURES - Suyog Rathi (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Due to its subcutaneous position, clavicle fracture is a common bone injury in the shoulder region. Treatment options for clavicle mid-shaft fractures include plate fixation, intramedullary K-wire fixation, and Steinmann pin fixation. The purpose of the current study was to examine a tertiary hospital’s precontoured locking compression plate treatment of midshaft clavicle fractures. Goals and objectives: The purpose of the current study was to examine a tertiary hospital’s precontoured locking compression plate treatment of midshaft clavicle fractures. Material and Methods: This study involved patients with isolated closed midshaft clavicle fractures with displacement > 2 cm, shortening > 2 cm, and Robinson classifications 2B1 and 2B2 who were aged 19 to 60 years, of either gender (displaced fractures). Results: 64 midshaft clavicle fractures were treated with precontoured locking compression plates at our institution during the trial period. The majority were male (78.26%), the mean age was 43.12 11.28 years, and the majority suffered road traffic accidents (81.50%) and unilateral clavicle fractures (96.43%). In the current study, the average surgery lasted 46.19 12.33 minutes, and a return to normal activities took 7.39 4.28 weeks. Dysthesia (6.50%), Wound dehiscence (3.26%), and Painful shoulder (9.59%) were complications reported. There were no obvious mobility restrictions or hypertrophic scars. Only 12 fractures (18.38%) needed 14 weeks to heal, which is faster than the average (53.26%). Excellent Constant scores were reported in 83.38% of patients during the 1-year follow-up. Conclusion: Precontoured locking compression plates are used in unstable displaced comminuted fractures in the middle part of the clavicle to provide fracture stability, promote early union, allow for early mobility, and avoid motion restriction and shoulder stiffness. Keywords: precontoured locking compression plates, comminuted fractures, midshaft clavicle, early union, early mobility.